1995
DOI: 10.1111/j.1469-8137.1995.tb03025.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2, soil nitrogen and turnover of fine roots

Abstract: SUMMARYIn most natural ecosystems a significant portion of carbon fixed through photosynthesis is allocated to the production and maintenance of fine roots, the ephemeral portion of the root system that absorbs growth-limiting moisture and nutrients. In turn, senescence of fine roots can be the greatest source of C input to forest soils. Consequently, important questions in ecology entail the extent to which increasing atmospheric CO^ may alter the allocation of carbon to, and demography of, fine roots. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
234
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(270 citation statements)
references
References 25 publications
32
234
1
3
Order By: Relevance
“…The positive correlations between below-ground starch concentration and percentage or number of ectomycorrhizas observed in this study reflect overall sink/source trends of the host, while the negative correlation between mycorrhiza and steady-state soluble carbohydrate concentration might reflect changes in demand and use by the fungal symbiont (Hacskaylo, 1973). Understanding sink/source relationships, particularly quantifying the flux of C between above-and below-ground plant tissues, might give a greater understanding of mechanisms regulating mycorrhizal response in elevated-COg environments (Zak et al, 1993;Pregitzer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive correlations between below-ground starch concentration and percentage or number of ectomycorrhizas observed in this study reflect overall sink/source trends of the host, while the negative correlation between mycorrhiza and steady-state soluble carbohydrate concentration might reflect changes in demand and use by the fungal symbiont (Hacskaylo, 1973). Understanding sink/source relationships, particularly quantifying the flux of C between above-and below-ground plant tissues, might give a greater understanding of mechanisms regulating mycorrhizal response in elevated-COg environments (Zak et al, 1993;Pregitzer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Under ambient CO2 levels, mycorrhizal infection can cause plants to assimilate more COg and to allocate a greater proportion of this assimilate to their root systems (Reid, Kidd & Ekwebelam, 1983). Extra C from elevated atmospheric COg can also enter the rhizosphere via root turnover and exudation Pregitzer et al, 1995). The possibility of additional C entering rhizospheres of plants growing under atmospheric COg enrichment has prompted researchers to hypothesize increased colonization by mycorrhizal fungi (Lamborg, Hardy & Paul, 1983) Effects of COg enrichment on colonization of plant roots by mycorrhizal fungi have received limited attention and results have been variable.…”
Section: Introductionmentioning
confidence: 99%
“…Because changes in plant tissue chemistry will affect decomposition rates (Meentemeyer 1978, Ryan et al 1990, Cotrufo and Ineson 1996, O'Neill and Norby 1996), elevated CO 2 could impact C turnover and storage in soils (Prior et al 1997c, Torbert et al 1997. Pregitzer et al (1995) suggested that increased rates of root turnover may occur in response to elevated CO2, and if coupled with increased C:N, could lead to increased belowground C storage.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen content also decreased in P. involutus. Finally, we note that elevated CO # can increase fine-root mortality (Pregitzer et al, 1995), which might be followed by a decrease in the life span of relatively long-lived ECM root tips and rhizomorphs.…”
Section: Life Span and Decomposition Of Mycorrhizal Tissuementioning
confidence: 99%
“…Nitrogen concentrations of hyphae from one P. involutus isolate were reported to increase with higher N availability in a culture experiment (Wallander et al, 1999), with possible shifts in decomposition rate. Additionally, root turnover can increase with N fertilization (Pregitzer et al, 1995 ;Majdi & Nylund, 1996), and this response could produce a corresponding decrease in the life span of ECM structures such as mycorrhizal root tips and rhizomorphs.…”
Section: Life Span and Decomposition Of Mycorrhizal Tissuementioning
confidence: 99%